”Monumentet”, en plats för kollektivets ceremonier? - Munkenberg, Betty-Ann (In Situ Archaeologica, 2002)
An Iron Age monument was built by an elite that on religious ground tried to strengthen its position. To display its power a new monumental element was erected in a setting that had been symbolically loaded for generations”. This is a hypothesis based on the results from the excavation at the Svarteborg 116 site in Bohuslän. The largest construction was the so-called ”monument” that measured 37 m in diameter. It was built on and around a small oval-shaped cliff at the lowest part of a minor grave field, in connection with a settlement from the Pre-roman Iron Age period. On the cliff, underneath the stone paving of the monument, rock carvings were encountered, together with marks of a wooden platform and hearths in the soil. The archaeological analysis of the Svarteborg 116 site has just started and in this article I discuss problems connected with dating the ”monument”. Six of seven graves on the site were classified as stone-settings. The oldest of them has been 14C-dated to 3440 ± 60 BP and the youngest to 1475 ± 55 BP. The ”monument” is probably the last construction erected on the burial ground.